Paleoecological and historical data as an important tool in ecosystem management. (15th April 2019) - Słowiński, Michał; Lamentowicz, Mariusz; Łuców, Dominika; Barabach, Jan; Brykała, Dariusz; Tyszkowski, Sebastian; Pieńczewska, Anna; Śnieszko, Zbigniew; Dietze, Elisabeth; Jażdżewski, Krzysztof; Obremska, Milena; Ott, Florian; et al.
Abstract: In recent decades, it has been observed that most forest fires in Europe were caused by people. Extreme droughts, which are more often prolonged, can increase the risk of forest fires, not only in southern Europe but also, in Central Europe. Nonetheless, catastrophic fire events are not well recognized in the Central European Lowlands (CEL), where large forest complexes are located. Knowledge of past fire activity in this part of Europe is scarce, although several fires have occurred in this area during the previous millennia. Large coniferous forest monocultures located in the CEL are highly susceptible to fires and other disturbances. Here, we present a case study from the Tuchola Pinewoods (TP; northern Poland), where large pine monocultures are present. The main aim of this study is to document the potential effects past land management has on modern day disturbance regimes using state-of-the-art paleoecological data, historical documents and cartographic materials. We then present a protocol that will help forest managers utilize long-term paleoecological records. Based on paleoecological investigations, historical documents, and cartographic materials, our results show that, in the past 300 years, the TP witnessed not only disastrous fires and but also windfalls by tornados and insect outbreaks. A change in management from Polish to Prussian/German in the 18th century led to the transformation of mixed forests into Scots pine monocultures with the purpose to allow better economic use of the forest. Those administrative decisions led to an ecosystem highly susceptible to disturbances. This article provides a critical review of past forest management as well as future research directions related to the impacts of fire risk on land management and ecosystem services: (a) habitat composition and structure (biodiversity); (b) natural water management; and (c) mitigation of climate changes. Designated forest conditions, management, and future fire risk are a controversial and highly debated topic of forest management by Forestry Units. More research will allow the gathering of reliable information pertinent to management practices with regard to the current fire risks. It is necessary to develop a dialog between scientists and managers to reduce the risk of fires in projected climate change. Highlights: Paleoecological and historical data should support forest management strategies. Long-term perspective helps define reference conditions and disturbance regimes of the forest. Paleoecological data strongly support forest management strategies and fire-risk assessment. Dialog between scientists and managers is crucial for proper ecosystem management.